(untitled) (Physical Education, Health and Social Sciences, 2025)
Background: End-stage renal disease (ESRD) is associated with a significantly increased risk of cardiovascular morbidity and mortality, with ST-elevation myocardial infarction (STEMI) representing one of the most serious cardiac complications. Due to the unique pathophysiological changes in ESRD, traditional cardiovascular risk factors may not fully predict STEMI in this population. Objective: To determine the prevalence of ST-elevation myocardial infarction (STEMI) among ESRD patients admitted with acute coronary syndrome (ACS) and to assess its association with baseline patient characteristics. Material and Methods: This descriptive cross-sectional study was conducted at the Inpatient Department of Shifa International Hospital, Islamabad, over a six-month period from November 2024 to April 2025. A total of 71 ESRD patients aged 30–60 years on maintenance hemodialysis for at least three months and admitted with ACS were included. Data were collected on demographics, comorbidities, and laboratory parameters. STEMI was diagnosed based on ECG changes and elevated troponin levels. Associations with baseline variables were assessed using the chi-square test. Results: Among 71 patients, the mean age was 46.72 ± 8.88 years, with a mean BMI of 25.43 ± 4.84. STEMI was diagnosed in 14 patients, yielding a prevalence of 19.7%. STEMI was more frequently observed in patients aged 30–40 years (28.6%), females (20.9%), obese individuals (27.3%), and non-smokers (22.2%); however, no association with age, gender, obesity, smoking, diabetes, or hyperlipidemia was statistically significant. Conclusion: STEMI is a common cardiac event in ESRD patients admitted with ACS. Traditional cardiovascular risk factors did not significantly predict STEMI in this cohort, suggesting the need to explore uremia-specific contributors.